2022
DOI: 10.21512/bbr.v13i1.7801
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perception and the Evaluation to Adopt Augmented Reality in Furniture Retail Mobile Application

Abstract: The importance of retailers to utilize interactive technology, such as Augmented Reality (AR), in their mobile applications is considered due to the change in consumer behavior from in-store to online. However, there is limited study in understanding consumer perception to evaluate the effectiveness of AR implemented by retailers during the COVID-19 pandemic in developing countries like Indonesia. The research examined the relationship between AR characteristics, consumer perception, and attitude toward AR in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Investigating consumer behavioral intention to purchase a certain product is essential to predict their actual behavior (X. . This is supported by previous research that stated that examining online purchase intention is a determinant of knowing consumer behavior in the online environment (Pascual-Miguel et al, 2015;Peña-García et al, 2020;Ramdani et al, 2022). Zhou et al (2021) found that image type significantly affects consumer attitude through its imagery elaboration.…”
Section: Consumer Attitude and Purchase Behaviorsupporting
confidence: 78%
“…Investigating consumer behavioral intention to purchase a certain product is essential to predict their actual behavior (X. . This is supported by previous research that stated that examining online purchase intention is a determinant of knowing consumer behavior in the online environment (Pascual-Miguel et al, 2015;Peña-García et al, 2020;Ramdani et al, 2022). Zhou et al (2021) found that image type significantly affects consumer attitude through its imagery elaboration.…”
Section: Consumer Attitude and Purchase Behaviorsupporting
confidence: 78%
“…Adapun, keterbatasan teknologi AR adalah tidak semua produk dapat terbantu oleh teknologi AR, sebagai contohnya produk yang menggunakan indera penciuman maupun indera sentuhan. Sehingga, teknologi ini terbatas digunakan oleh produk yang mengutamakan indera penglihatan atau visual seperti pengaplikasian AR di produk kecantikan (lipstick, blush on dan sebagainya), produk garmen dan turunannya (seperti pakaian dan aksesoris), serta produk furniture dan turunannya [2][3][4].…”
Section: Pendahuluanunclassified
“…Hasil dari uji hipotesis menunjukkan bahwa hipotesis keempat yang menyatakan sikap terhadap AR dalam pembelian online terhadap intensi pembelian diterima yakni ditunjukkan dengan nilai sig < 0,05% (sig 0,00) dengan nilai estimate 0,627. 2022) juga menyatakan bahwa sikap terhadap AR berpengaruh positif signifikan pada intensi mengadopsi AR dalam aplikasi mobile retail furniture di Indonesia [3]. Berdasarkan hasil pengolahan, pernyataan "Saya suka ide berbelanja online dengan teknologi AR" memiliki varians tertinggi yang mengimplikasikan bahwa responden terbuka dengan berbagai perkembangan teknologi AR ketika melakukan pembelian online.…”
Section: Attitude Toward Ar In Online Purchaseunclassified
“…According to data from the Indonesian Internet Service Providers Association (APJII), the number of internet users in Indonesia in 2020 reached 196.7 million people, with the percentage of internet users for online shopping at 88.1%1. This shows that online shopping has become one of the popular and preferred activities by the Indonesian people [1,2]. One of the technologies that can enhance the online shopping experience is augmented reality (AR).…”
Section: Introductionmentioning
confidence: 99%